Comprehensive multiomics analysis identifies PYCARD as a key pyroptosis-related gene in osteoarthritis synovial macrophages - Yao, Zihao; Li, Yuexin; Mai, Hanwen; Wang, Zhuolun; Zhang, Haiyan; Cai, Daozhang; Wang, Xiangjiang (Frontiers in Immunology, 2025)
BackgroundOsteoarthritis (OA) is a chronic joint disease that significantly impairs quality of life. Synovitis plays a pivotal role in OA progression, and pyroptosis, a form of programmed cell death associated with innate immune inflammation, may contribute to the pathogenesis of OA synovitis. Nevertheless, the precise role of pyroptosis in OA pathogenesis remains poorly understood.MethodsWe performed an analysis of bulk RNA sequencing data to examine the expression profiles of pyroptosis-related genes in the OA synovium. A LASSO-Cox regression model was employed to identify pivotal genes. Single-cell RNA sequencing data were used to validate the expression of these genes in specific synovial cell clusters. Differentially expressed genes (DEGs) in macrophages with high or low expression levels of core genes were subjected to enrichment analysis. A protein-protein interaction (PPI) network was constructed to identify hub genes, and potential therapeutic compounds were predicted. Consensus clustering analysis was performed to examine the correlations between hub genes and disease status. After identifying PYCARD as the core pyroptosis gene in OA macrophages, we assessed the expression levels of PYCARD in the OA synovium and validated the expression of PYCARD and its related core genes in M1 macrophages.ResultsA total of twenty pyroptosis-related DEGs were identified, and six core genes were selected through LASSO regression. PYCARD was identified as the key pyroptosis gene in macrophages. Furthermore, 57 therapeutic compounds targeting these genes were predicted. Validation confirmed the upregulation of PYCARD in the OA synovium and M1 macrophages.ConclusionPYCARD was identified as the core pyroptosis gene in OA macrophages, and 57 potential therapeutic compounds were identified. This study offers valuable insights into potential treatment targets for OA.